Extrapulmonary Findings and Malignancies in Participants Screened With Chest CT in the National Lung Screening Trial - Nguyen, Xuan V; Davies, Louise; Eastwood, James D; Hoang, Jenny K (Journal of the American College of Radiology, 2017)
The aim of this study was to measure the prevalence of clinically significant extrapulmonary findings on chest CT for lung cancer screening in the National Lung Screening Trial (NLST). Prospectively acquired data on 17,309 participants who underwent low-dose screening chest CT from August 2002 through September 2007 during the NLST were retrospectively analyzed for extrapulmonary findings. NLST radiologist readers coded such findings as "minor" or "potentially significant." On the basis of review of recorded text descriptions, extrapulmonary findings were assigned to five organ groupings (cardiovascular, thyroid, adrenal, renal, and hepatobiliary). Extrapulmonary malignancies diagnosed during screening were also identified from medical and vital status records in the same population. The prevalence rates of organ-specific findings and newly diagnosed extrapulmonary malignancies were calculated. Exemption from human subjects research review was obtained. Extrapulmonary findings were noted in 58.7% of CT-screened participants, and 19.6% had findings coded as potentially significant. The prevalence of potentially significant abnormalities was highest for cardiovascular findings (8.5%), followed by renal (2.4%), hepatobiliary (2.1%), adrenal (1.2%), and thyroid (0.6%) findings. Sixty-seven of 17,309 participants (0.39%) had primary extrathoracic cancers diagnosed during screening. The prevalence of cancers among screened participants was 0.26% (n = 45) for kidney, 0.08% (n = 14) for thyroid, and 0.05% (n = 8) for liver cancers. One in five patients screened with CT for lung cancer will have extrapulmonary findings potentially requiring further evaluation. Indiscriminate workups of incidental extrapulmonary findings could place a significant burden on the health care system with little benefit because extrapulmonary malignancies diagnosed during screening are uncommon. Radiologists reporting screening CT should be familiar with existing recommendations for incidental findings from the ACR white papers.